2014
DOI: 10.1242/dev.108019
|View full text |Cite
|
Sign up to set email alerts
|

Efficient homologous recombination-mediated genome engineering in zebrafish using TALE nucleases

Abstract: Custom-designed nucleases afford a powerful reverse genetic tool for direct gene disruption and genome modification in vivo. Among various applications of the nucleases, homologous recombination (HR)-mediated genome editing is particularly useful for inserting heterologous DNA fragments, such as GFP, into a specific genomic locus in a sequence-specific fashion. However, precise HR-mediated genome editing is still technically challenging in zebrafish. Here, we establish a GFP reporter system for measuring the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 52 publications
1
122
0
Order By: Relevance
“…It is widely accepted that DSBs mediated by SSNs at a target gene stimulate GT in several organisms, such as mammals (Pauwels et al, 2014), fish (Shin et al, 2014), insects (Lin et al, 2014), and plants (Puchta and Fauser, 2013;Voytas and Gao, 2014). Here, the induction of DSBs mediated via SSNs in a lig4 mutant background provided evidence that the SDSA-like pathway was enhanced by the disruption of cNHEJ in rice.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It is widely accepted that DSBs mediated by SSNs at a target gene stimulate GT in several organisms, such as mammals (Pauwels et al, 2014), fish (Shin et al, 2014), insects (Lin et al, 2014), and plants (Puchta and Fauser, 2013;Voytas and Gao, 2014). Here, the induction of DSBs mediated via SSNs in a lig4 mutant background provided evidence that the SDSA-like pathway was enhanced by the disruption of cNHEJ in rice.…”
Section: Discussionmentioning
confidence: 79%
“…DSB repair via HR using exogenous donor DNA, resulting in the replacement or insertion of new nucleotide sequences, is referred to as gene targeting (GT). Consequently, SSN-mediated DSB induction at the target locus could lead to an increased frequency of GT in several organisms (Puchta and Fauser, 2013;Lin et al, 2014;Pauwels et al, 2014;Shin et al, 2014;Voytas and Gao, 2014).…”
mentioning
confidence: 99%
“…2J, arrowhead). Additionally, an endogenously tagged sox2-p2a-sfGFP reporter line (Shin et al, 2014) exhibits fluorescence in posterior notochord cells, which do not express sox2 transcript or protein, indicating that at least some notochord cells were previously sox2 positive (Fig. 2K,K′, arrowheads).…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, Zu et al reported the first HR gene-targeting event using TALENs and a double stranded vector containing an eGFP cassette flanked by long homology arms and a germ line transmission rate of 1.5%. More recently many other laboratories have developed various methods to generate knockin alleles by HR followed by CRISPR/Cas9-induced DSB, using as donor single stranded DNA, circular or linear plasmids with short (~40 bp) or long (800-1000 bp) homology arms (Hruscha et al 2013;Hwang et al 2013a;Irion et al 2014;Shin et al 2014;He et al 2015;Hisano et al 2015). Although these methods were proven possible, their efficiency remains variable.…”
Section: Crispr/cas9-mediated Knockin Approaches In Zebrafishmentioning
confidence: 99%